Pengaruh Kompensasi Terhadap Turnover Intention dengan Kepuasan Kerja Sebagai Variabel Intervening pada PT. Asta Jawa Dwipa Surabaya - Sekar Aulia Puspitasari; Endang Iryanti; Daisy Marthina Rosyanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The objective of this research is to determine the effect of compensation on turnover intention with job satisfaction as an intervening variable in PT. Asta Jawa Dwipa, Surabaya. The method in this study uses an associative quantitative approach with the distribution of questionnaires and short interviews as data collection techniques. The population in this study is all employees of PT. Asta Jawa Dwipa Surabaya which is in the field of technicians using a saturated sampling technique, which is 72 employees. Data analysis uses Partial Least Square (PLS). Accordingly of this research show that compensation has a significant negative effect on turnover intention and job satisfaction can mediate compensation for turnover intention at PT. Asta Jawa Dwipa, Surabaya.